Rewriting the Soul : Multiple Personality and the Sciences of Memory - Hacking, Ian (Book collections on Project MUSE., 2001)
Twenty-five years ago one could list by name the tiny number of multiple personalities recorded in the history of Western medicine, but today hundreds of people receive treatment for dissociative disorders in every sizable town in North America. Clinicians, backed by a grassroots movement of patients and therapists, find child sexual abuse to be the primary cause of the illness, while critics accuse the "MPD" community of fostering false memories of childhood trauma. Here the distinguished philosopher Ian Hacking uses the MPD epidemic and its links with the contemporary concept of child abuse.